Respectful focused antenatal care and associated factors among pregnant women who visit Shashemene town public hospitals, Oromia region, Ethiopia: a cross‐sectional study - Daniel Adane; Agegnehu Bante; Biresaw Wassihun (BMC, 2021)
Abstract Background Focused antenatal care is the most significant and inclusive care given to pregnant women to promote and maintain the optimal health of the mother and the fetus. Providing respectful care during focused antenatal care is believed to be the most important cost-effective interventions to increase maternity service utilization. Therefore, this study was aimed to assess respectful focused antenatal care and associated factors among pregnant women who visit Shashemene town public hospitals, Oromia region, Ethiopia, 2019. Methods Institution-based cross-sectional study was conducted from July-August, 2019. A total of 423 pregnant mothers were selected using a systematic sampling technique. Data were collected using structured and pre-tested interviewer-administered questionnaires. Data entry and analysis were made using Epi Info version™ 7 and Statistical Package for Social Science (SPSS) version 24.0 respectively. Both bivariate and multivariate logistic regression analyses were used to identify associated factors. Statistical significance was declared at a p value of < 0.05 with a 95% confidence level. Results A total of 420 women have participated in the study, making a response rate of 99.5%. About 63% of participants received respectful care during focused antenatal care. Having no formal education [AOR = 8.3(95%CI 9.85-17.47)], low average monthly income [AOR = 3.16 (95%CI 1.52-6.57)], having unplanned pregnancy [AOR = 9.90 (95%CI 3.48-8.16)] and being multigravida [AOR = 8.82 (95%CI 2.90-6.80)] were significantly associated with respectful focused antenatal care. Conclusions The study findings indicate that respondents' respectful focused antenatal care is mainly affected by educational level, average family monthly income, having an unplanned pregnancy, and gravidity. Providing acceptable, quality, and honorable care for all women regardless of educational status, family income, and status of pregnancy is very crucial to entice more mothers to the health facility.